2016
DOI: 10.3390/catal6090142
|View full text |Cite
|
Sign up to set email alerts
|

Solventless Synthesis of Quaterphenyls and Terphenyls from Chalcones and Allylsulfones under Phase Transfer Catalysis Conditions

Abstract: Abstract:Easily available chalcones and allyl sulfones along with cheap solid NaOH and polyethyleneglycol (PEG) 1000 have been used to directly generate the meta-terphenyl or quaterphenyl motifs under Phase Transfer Catalysis solventless conditions. The new approach provides an economic and environmentally friendly solution to removal of hazardous bases as well as organic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…17 BTPS (6) denotes OLED use. 18,19 The remaining two cyclophanes, 7 and 8, are employed as metal trapping agents due to the hollow hole that exists inside the structural framework. 20,21 Furthermore, polyfunctionalized derivatives of m-terphenyl are employed as strong UV lters.…”
Section: Introductionmentioning
confidence: 99%
“…17 BTPS (6) denotes OLED use. 18,19 The remaining two cyclophanes, 7 and 8, are employed as metal trapping agents due to the hollow hole that exists inside the structural framework. 20,21 Furthermore, polyfunctionalized derivatives of m-terphenyl are employed as strong UV lters.…”
Section: Introductionmentioning
confidence: 99%
“…12 In recent decades, the synthesis of such LCs carried out with the help of synthetic methods that do not use metal catalysis has been being widely carried out. [13][14][15] Previously, we synthesized new anisotropic terphenyl derivatives and demonstrated that they form smectic and nematic phases in a wide temperature range, namely 8-((4 00 -((1R,4S)-4butylcyclohexyl) -2 0 -chloro-[1,1 0 ,4 0 ,1 00 -terphenyl]-4-yl)oxy)oct-1en-3-one (TERPh-VK) and 6-((4 00 -((1R,4S)-4-butylcyclohexyl)-2 0chloro-[1,1 0 :4 0 ,1 00 -terphenyl]-4-yl)oxy) hexanoic acid (TERPh-COOH). 16 As for TERPh-VK, the double bond disappears under heating.…”
Section: Introductionmentioning
confidence: 99%